Les Bagnoles à L'Isle-sur-la-Sorgue Un site majeur du Néolithique moyen en Vaucluse - van Willigen, Samuel; Bailly, Maxence; Röder, Brigitte; Schibler, Jörg; Schmitt, Aurore (Préhistoires de la Méditerranée, 2020)
The archaeological site of Les Bagnoles is located in the territory of the town of L'Isle-sur-la-Sorgue (84). It was discovered in 2006, following an archaeological diagnostic, and then excavated between 2012 and 2015 on an area of 1.5 ha as part of a planned excavation project conducted by the universities of Basel and Aix-Marseille and supported by the PACA regional Archaeology Service. The main phases of occupation of the site are dated to the Middle Neolithic period. According to sedimentology and carpology data, these occupations are part of an natural environment of active alluvial plains. The most remarkable results are linked to the discovery of several cremation graves dating from the end of the 5th millenium BC, located within a possible burial space dedicated to funerals and commemorative ceremonies, and three Neolithic water wells which, exceptionally, still contained many organic remains preserved in wetlands. Put in their regional context, theses remains and the abundant furniture unearthed on the site considerably broaden our knowledge of the farming and livestock communities of the Mediterranean Neolithic and the environment in which they evolve.